Further fine mapping and candidate gene prediction for a new restoring fertility gene Rf(fa) in rice - Yu Li; Xiaomi Chen; Tao Lan; Jing Zhang; Ziheng Chen; Wenting Yang; Xinmei Lin (Czech Journal of Genetics and Plant Breeding, 2022)
Rf(fa), a new restoring fertility gene in rice, was previously located to a large region on Chromosome 10. The large number of genes within the region made cloning of Rf(fa) difficult. To perform the cloning and further elucidate the molecular mechanism, we reconstructed a mapping segregation population (BC1F1) of 12 000 plants. Using the population and polymorphism of simple sequence repeat (SSR) molecular markers, we finally mapped Rf(fa) between the two SSR molecular markers MM2000 and RM25658, within a 78.87 kb region. By de novo sequencing of a restoring line of CMS-FA hybrid rice, we obtained the genomic sequence of the mapping region, which provided the basis for the prediction of the candidate gene(s) of the target gene and for the comparison of genomic sequence differences between wild and cultivated rice. Within the mapping region, the genomic sequence of the wild rice was significantly different from that of cultivated rice. There were ten genes in the final mapping region. A pentatricopeptide repeat (PPR) protein gene was predicted as the candidate gene of Rf(fa). Our results laid a solid foundation for the final cloning and molecular mechanism analysis of the gene. The identified molecular markers tightly linked to Rf(fa) will facilitate the marker assisted selection in breeding of CMS-FA hybrid rice.